ESOPHAGEAL VARICES AND ASSOCIATED FACTORS IN CIRRHOTIC PATIENTS WITH HEPATITIS C - Ali, Saira Muhammad; Farrukh, Syed Zea Ul Islam; Haqqi, Syed Afzal Ul Haq; Siddiqui, Arif Rasheed; Qadri, Muhammad Zahid; Niaz, Saad Khalid (Journal of Ayub Medical College Abbottabad, 2022)
Background: Infection with hepatitis C virus is reported to have infected almost 71 million people worldwide. This study was done to assess the frequency and associated factors leading to oesophageal varices in patients presenting with hepatitis C related liver cirrhosis. Methods: A cross-sectional study was conducted at Patel Hospital, Karachi, Pakistan from 9th May to 5th October 2019. Patients of either gender having age >20 years presenting with HCV related liver cirrhosis, and Child Pugh class A, B and C were consecutively enrolled in the study. Data on variables like: age, gender, Childs Pugh Score (A/B/C), smoking status, laboratory characteristics like hemoglobulin (Hb), TLC, platelets, serum albumin level, cholesterol, alkaline phosphate (ALK), alkaline transaminase (ALT), ascites and presence of oesophageal varices was recorded and analysed using SPSS-21.0. Results: Out of 167 patients, mean age was 44.86±14.74 years. Eight-nine (53.3%) of the patients were males. The mean duration of cirrhosis was 5.78±1.10 months. Thrombocytopenia was observed in majority (n=130, 77.8%) of the patients. There were 33 (19.8%) patients with Child Pugh score A while Child-Pugh score B and C was found in 67 (40.1%) each. The frequency of oesophageal varices was 141 (84.4%). A significantly higher proportion of oesophageal varices were found among thrombocytopenic patients (p<0.001), ascites (p-0.024), and having C Child-Pugh score (p 0.012). Conclusion: Oesophageal varices were found in a considerable proportion. Thrombocytopenia, ascites and Child-Pugh class C were found as leading contributing factors to oesophageal varices.